The Development of Indonesia's Halal Industry from a Macroeconomic Perspective: A Critical Review - Ken Ayu Citra; Veithzal Rivai Zainal; Nurwahidin Nurwahidin; Mohammad Izdiyan Mutaqqin; Nur Fatwa (Dinasti Publisher, 2025)
Indonesia, as the country with the largest Muslim population in the world, has big aspirations to become a global halal industry hub. The halal industry encompasses various sectors – from food/beverages, Muslim fashion, halal tourism, cosmetics, pharmaceuticals to Islamic finance – all of which are run in accordance with sharia principles. A macroeconomic review of the development of the halal industry in Indonesia is important given its potential contribution to economic growth, job creation, and Indonesia's position in the global halal economy. This paper will examine five key aspects: the macroeconomic conditions of the halal industry in Indonesia and globally, government support, the role of young people, and a case study of the halal fashion industry, accompanied by a critical discussion of the pros and cons of halal industry development in Indonesia. This analysis draws on the findings of five key studies: AlBanna (2019), Hudaefi & Jaswir (2019), Rusydiana (2023), Julianti et al. (2024), and Rini et al. (2025), to provide an integrated and up-to-date academic perspective.